Reduction of the 28-Day Readmission Rate for Children with Sickle Cell Disease. (1st June 2016) - Beck, C; Kirby-Allen, M; Cheong, M; Langrish, K; Clarke, A; Nishimura, C; Palmer, M; Gervais, A; Moloney, J; Mack, L
Abstract: BACKGROUND: Failure to provide coordinated care may lead to inefficiencies and negatively impact the quality of patient care provided. For children with sickle cell disease (SCD) at our tertiary care children's hospital, traditionally hematology has provided ambulatory and consultative care, and general paediatrics has provided inpatient management. We fostered collaboration and used quality improvement (QI) methods to improve patient care, using hospital readmission rates as our primary QI measure. OBJECTIVES: To reduce the 28-day readmission rate for pediatric patients with SCD from current levels (18.5%) to 14% over a 12-month period. DESIGN/METHODS: An interdisciplinary team diagnosed and developed strategies to address gaps in care coordination. A chart audit was conducted and a process map of the hospital journey was created to identify opportunities for improvement. Based on impact and effort, the following strategies were prioritized and implemented: standardization of pain management, support for patients at highest risk of readmission, streamlining the discharge process, and increased use of hydroxyurea. Quarterly data were abstracted via Health Records from the Discharge Abstract Database (DAD). The measure of interest was the percentage of patients (0-18 years of age) with SCD and crisis readmitted with the same or related diagnosis within 28 days. Patients were identified using the ICD10 code D57.0; "crisis" includes vaso-occlusive crisis, acute chest syndrome, and splenic sequestration. Individual process measures reflecting our multiple improvement strategies were also collected. RESULTS: From fiscal year 2013-14 to 2014-15, the total number of patient admissions for SCD decreased from 173 to 166. The readmission rate, as defined above, decreased from 18.5% to 10.8%. Other measures specifically reflecting our improvement strategies continue to be followed with ongoing process improvement. CONCLUSION: A multi-modal strategy approach aimed at coordinating care has led to a decrease in rate of readmission for children with SCD below the established target. Ongoing monitoring will be required to ensure sustainability of this result. Further opportunities for standardization of care for this patient population include updating relevant clinical practice guidelines and order sets; implementing "pain plans" for transition home; and optimizing outpatient follow-up.